2021
DOI: 10.15832/ankutbd.959820
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Microbiological Changes in Non-Sulfitted Dried Apricots as Affected by Storage Condition

Abstract: This study was conducted to determine the changes in the physicochemical and microbiological qualities of the non-sulfited sun dried apricots (NSDAs) at three different moisture contents (MCs, 13.7, 23.5 and 27.0%) and at four different storage temperatures (4, 10, 20, and 30 °C) for 12 months in bulk and packaged samples. NSDAs were subjected to physical (moisture, water activity, pH and reflectance colour values), chemical (browning formation, β-carotene, and acidity), and microbial (counts for total aer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…The measurements were recorded L* (Lightness), +a* (redness), +b* (yellowness), C* (Chroma), and h° (hue angle) color coordinates. The total color changes (ΔE) were calculated using L*, a* and b* coordinates according to the following equations ( Güzel et al, 2022 ). ΔΕ = [(Δa) 2 + (Δb) 2 + (ΔL) 2 ] 0.5 …”
Section: Methodsmentioning
confidence: 99%
“…The measurements were recorded L* (Lightness), +a* (redness), +b* (yellowness), C* (Chroma), and h° (hue angle) color coordinates. The total color changes (ΔE) were calculated using L*, a* and b* coordinates according to the following equations ( Güzel et al, 2022 ). ΔΕ = [(Δa) 2 + (Δb) 2 + (ΔL) 2 ] 0.5 …”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the color of dried fruits changes due to the formation of brown color, which is affected by temperature and relative humidity. Research shows that the formation of brown color in dried fruits increases with increasing temperature and decreasing humidity (Güzel et al, 2022). Baini and Langrish (2009) dried bananas at 70 degrees Celsius and relative humidity from 15% to 40% and found that the change in redness of the sample dried at 15% relative humidity was 67% higher than that of the sample dried at 40% relative humidity.…”
Section: Introductionmentioning
confidence: 99%